2019
DOI: 10.1016/j.canlet.2018.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology-based photoimmunological therapies for cancer

Abstract: Phototherapy is a non-invasive or minimally invasive therapeutic strategy. Immunotherapy uses different immunological approaches, such as antibodies, vaccines, immunoadjuvants, and cytokines to stimulate the host immune system to fight against diseases. In cancer treatment, phototherapy not only destroys tumor cells, but also induces immunogenic tumor cell death to initiate a systemic anti-tumor immune response. When combined with immunotherapy, the effectiveness of phototherapy can be enhanced. Because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 121 publications
(117 reference statements)
0
38
0
1
Order By: Relevance
“…Light has been used in the clinical setting since the beginning of the 20th century, and phototherapies have been widely used to treat skin diseases (such as lupus) and cancers [109,110]. Currently, phototherapies are divided into photodynamic therapy (PDT) and photothermal therapy (PTT).…”
Section: Photo-chemotherapymentioning
confidence: 99%
“…Light has been used in the clinical setting since the beginning of the 20th century, and phototherapies have been widely used to treat skin diseases (such as lupus) and cancers [109,110]. Currently, phototherapies are divided into photodynamic therapy (PDT) and photothermal therapy (PTT).…”
Section: Photo-chemotherapymentioning
confidence: 99%
“…A safe and effective immunotherapy with great controllability and sensitivity can be achieved by developing novel drug delivery platforms based on nanotechnology and material science. [264][265][266][267][268][269][270] The cascaded synergistic effects of photodynamic-immunotherapy can provide a promising strategy to inhibit both primary lesions and distant metastases, which can be hardly achieved by conventional PDT with limited immunologic effects. [256] Moreover, the combination of immunotherapy and PDT has attracted an increasing attention due to the potential systematic antitumor immunity after PDT.…”
Section: Postoperative Immunotherapy For Long-term Antitumor Effectsmentioning
confidence: 99%
“…When summarizing a large number of reports from photothermal‐immunotherapy, we found that control of photothermal temperature was very important for enhancing the immunogenicity of the tumor. It was generally believed that 39–42°C was beneficial for the induction of ICD (Li, Li, et al, ; Toraya‐Brown & Fiering, ). When the temperature was higher (>50°C), it showed no selection in killing cancer cells and non‐cancerous stromal cells (Toraya‐Brown & Fiering, ).…”
Section: Nanomaterials For the Regulation Of Cancer Immunity Cyclementioning
confidence: 99%